Protective Effects of Gynostemma pentaphyllum Saponins on Liver Injury in Guinea Pigs of Hyperlipemia Based on Oxidative Stress - Tianyi DAI; Donglian LIU; Xingmin QIN; Chengling GAO; Jiayi LI; Hailing KUANG (Shipin gongye ke-ji)
Objective: To observe the protective effects of Gynostemma pentaphyllum saponins (GPs) on liver injury in guinea pigs of hyperlipemia based on oxidative stress. Methods: A total of 32 guinea pigs were randomly divided into a model group, a low dose GPs group (85 mg/kg), a high dose GPs group (170 mg/kg), and a simvastatin group (1.5 mg/kg), with 8 animals in each group. All animals were fed with high-fat diet for 5 weeks to prepare a hyperlipemia model. At the same time, 8 guinea pigs were set up as a normal group and given regular feed. From the 6 th week onwards, hyperlipemia model guinea pigs were fed with high-fat diet go on, and were given intragastric administration at the same time, once a day for 4 consecutive weeks. The normal group and model group were given equal amount of normal saline. The body mass, body length, and Lee's index of each group of guinea pigs were measured weekly. After the experiment, the levels of total TC, TG, HDL and LDL of guinea pigs were measured. The liver mass, liver to body ratio, and fasting blood glucose of guinea pigs were measured. The levels of SOD, MDA, CAT and GSH-px in the liver were detected. HE and oil red staining were used to observe the pathological and morphological changes of guinea pig liver tissue. Immunofluorescence method was used to observe the protein expression of Nrf2 and HO-1 in the liver of guinea pigs. Results: At the end of the experiment, compared with the model group, the high dose and low dose group of GPs significantly decreased the level of the body mass (P<0.01) in hyperlipidemic guinea pigs. The low dose group of GPs significantly decreased the Lee's index (P<0.05). The high dose group of GPs significantly decreased the Lee's index (P<0.01). The low dose group of GPs significantly decreased the levels of TG and LDL in serum (P<0.05, P<0.01). The high dose group of GPs significantly decreased the levels of TC, TG, and LDL in serum (P<0.05, P<0.01). The low dose group of GPs significantly decreased the level of MDA in the liver tissue (P<0.05). The high dose group of GPs significantly increased the level of SOD (P<0.05), and decreased the level of MDA (P<0.01) in the liver tissue. Pathology showed that the high dose group of GPs reduced the fatty degeneration and lipid droplet accumulation in the hepatocytes of hyperlipidemic guinea pigs. The fluorescence expression of Nrf2 and HO-1 proteins in both the high and low dose groups of GPs significantly increased (P<0.01). Conclusion: GPs would have a good hepatic protective effect through significantly improve oxidative stress levels by activate the Nrf2/HO-1 signaling pathway in guinea pigs of hyperlipemia.